Synthesis and in vitro Antibacterial Activity of Some Novel 2-Amino-4, 6-D Derivatives - S.A. Rahaman (Journal of Sciences, Islamic Republic of Iran)
Heterocyclic systems are one of the most important classes of organic compounds present in nature or synthesized in laboratory. These compounds posses an array of biological activities and are employed in the treatment of commonly occurring diseases. Keeping this in view, some new 2-amino-4,6-diarylpyrimidine from chalcones were synthesized. Eight novel 2-amino-4,6-diarylpyrimidine derivatives have been prepared by condensation of chalcone derivatives with guanidine hydrochloride. The structures of the synthesized compounds were assigned on the basis of elemental analysis, IR spectra, 1H NMR and Mass spectral data. These compounds were screened for their antibacterial activity. The recorded zone of inhibition showed significant antibacterial activity when compared with reference standard Sparfloxacin.